Analysis of static and dynamic capacity in Paraná State, Brazil (Acta Scientiarum. Agronomy, 2020)
This study had two objectives - firstly, to analyze the total static and dynamic capacity of agricultural storage in Paraná State, Brazil and secondly, to verify if the storage followed the growth of grain production. The study was performed by mesoregion for the 2013/2014 and 2014/2015 crop years. The methodology used was descriptive from an agricultural database of the Secretariat of Agriculture and Supply (SEAB), of the National Register System of Storage Units (SICARM), interviews were also made with agroindustrial cooperatives and official agencies. It was identified that in Paraná State there is an insufficiency of 17.75% of total static capacity of warehouses to comply with the total grain production (soybean, 1st and 2nd corn crops, and wheat). The results showed that the total dynamic capacity of warehouses is sufficient in the mesoregions of Eastern Center, Southern Center, Northern Center, and Metropolitan. Therefore, storage units vary uniformly in most municipalities, not following the growth of total grain production in the state of Paraná.